Título Padrão - Dias, Diogo Henrique Bispo (Argumentos - Revista de Filosofia, 2015)
Logical pluralism is the claim that there is more than one adequate logic. Many authors consider Carnap as one of the forerunners of logical pluralism. More than that, they claim that Carnap’s Principle of Tolerance consists in one of the first explicit formulations a logical pluralism. Nonetheless, there is little detailed investigation to evaluate if the Principle of Tolerance necessarily implies a logical pluralism, and if so, of which kind. The aim of this paper is to analyze the Principle of Tolerance, as well as its context, and to investigate the relation between such principle and logical pluralism.